Εντροπη: Shame and Identity Formation in the Letters of Ignatius of Antioch - Chan, Yi-Sang Patrick (Religions, 2024)
Since the 1980s, biblical scholars have started to employ the framework of “honor and shame” to study the culture of the ancient Mediterranean region. However, this application of the social–scientific honor–shame model has led to “massive generalizations of ‘honor’ and ‘shame’”. In particular, when focusing on the concept of honor/shame rather than its lexemes, the social–scientific school ignores the nuanced nature of each Greek word group related to shame. By studying classical Greek literature, Douglas Cairns further points out a puzzling situation that the word group αἰδώς contains polarized meanings of both “to shame” and “to respect”. In this paper, we examine the puzzling double meanings of “to shame/to respect” by focusing on the use of the word group ἐντροπή in the letters of Ignatius of Antioch. This paper argues that the word group ἐντροπὴ serves a rhetorical purpose of protecting the church’s identity by rejecting beliefs/customs that are unacceptable to Christianity and promoting unity in the churches through obedience to church authorities. This paper also explores the fundamental epistemological issue of understanding emotion words in its ancient context. It provides a provisional definition for ἐντροπή, that it is a self-inhibitory emotion of sensitivity to one’s proper place in social interaction to protect one’s self-image.